Effects of maternal exposure to bisphenol AF on emotional behaviors in adolescent mice offspring. (November 2017) - Gong, Miao; Huai, Ziqing; Song, Han; Cui, Lingyu; Guo, Qingjun; Shao, Juan; Gao, Yuan; Shi, Haishui
Abstract: Exposure to bisphenol A (BPA), one kind of environmental endocrine disruptors (EEDs), exerted significantly detrimental effects on neuro-endocrinological system and related disorders, such as memory dysfunction and depression. Bisphenol AF (BPAF), a newly introduced chemical structurally related to BPA, is used extensively. BPAF has stronger estrogenic activities than BPA. However, the potential neurotoxicological effects of BPAF are still elusive. The present study aimed to investigate the potential effects of maternal BPAF exposure during pregnancy on emotional behaviors of adolescent mice offspring. In male adolescent offspring, maternal exposure to BPAF (0.4, 4.0 mg kg −1, intragastrically administration) induced significant anxiety- and depressive-like behaviors, assessed by open field test (OFT), novelty-suppressed feeding test (NSF), sucrose preference test (SPT), tail suspension test (TST) and forced swimming test (FST). In female adolescent offspring, BPAF exposure at 0.4 mg kg −1 dose reduced the latency to feeding in the NSF test, while increased the floating time in the FST. Maternal BPAF exposure decreased the recognition index in the long term memory (LTM) test in both sexes, while only decreased the freezing time of male offspring in the contextual fear conditioning (CFC) task. These results indicate that maternal exposure to BPAF significantly affect emotion-related behaviors in adolescent mice offspring, and the male offspring with a higher probability to develop symptoms of anxiety and depression and to suffer memory impairment after maternal exposure to BPAF. Highlights: Maternal exposure to BPAF increased body weight in adolescent mice offspring. Maternal BPAF exposure affected anxiety-like behaviors of adolescent mice offspring. BPAF exposure affected depressive-like behaviors of adolescent mice offspring. Maternal exposure to BPAF impaired memory formation in adolescent mice offspring. Adolescent male offspring are more sensitive to BPAF exposure than female offspring.